(untitled) (MAUSAM, 1978)
Quasi-synoptic latent heat fluxes have been computed over the Arabian Sea for the period 20 June to 19 July 1963, During this same period, the monsoon rainfall at the west coast of India was measured and found to be divided into three distinct phases: preintense, intense and postintense. Whereas the correlation between the latent heat of evaporation over the Arabian Sea and the intensity of rainfall at the west coast of India is generally good, the computations also show that precipitation over the central and eastern Arabian Sea exceeds the moisture that evaporates into the atmosphere from the Arabian Sea. The results of the study suggest that while latent heat exchanges over the Arabian Sea playa significant role in the rainfall patterns at the west coast of India, a cause-and effect relationship is not clear.